Knowledge, attitude, and intended practice of abortion among medical students in Thailand after the amendment of the Thai abortion law - Rada Poolkumlung; Ratthapong Rongkapich; Natchanika Sinthuchai; Somsook Santibenchakul; Vorachart Meevasana; Unnop Jaisamrarn (Elsevier, 2023)
Objectives: Following the amendment of the Thai abortion law in February 2021, the authors conducted an anonymous survey to assess knowledge, attitude, and intended practice toward abortion among fifth-year medical students at Chulalongkorn University. Study design: The authors developed a self-administrated questionnaire consisting of three parts: knowledge of the recently amended Thai abortion law, attitude toward abortion, and intended practices. Pilot testing showed a high Cronbach's alpha and test-retest reliability coefficient. Results: Of the 292 surveyed medical students, 70% completed the questionnaire. The mean ± standard deviation of the knowledge part was 6.9 ± 1.8, of which the maximum score was 10. Nearly half of the participants (45.6%) answered at least 80% of the knowledge statements correctly. Sixty-four percent of participants answered correctly on the gestational limit for first-trimester abortion. Around one-third of participants answered correctly on the gestational limit for second-trimester abortion. Most participants (86.8%) agreed that abortion is a woman's right. The most acceptable conditions for abortion were pregnancy as a result of rape (93%) and serious anomalies that cause a nonviable neonate (95.6%). Conclusions: Participants exhibited a lack of understanding regarding the legal gestational limit, which is a key aspect of the amendment. The findings of this study urge medical schools to emphasize the revised Thai abortion law in the Obstetrics and Gynecology curriculum. Implications: Our results show that encouraging medical students to have up-to-date knowledge regarding the amendment of Thai abortion law may support their future decision to provide safe abortion services.